2015
DOI: 10.1097/scs.0000000000001557
|View full text |Cite
|
Sign up to set email alerts
|

External Dacryocystorhinostomy With or Without Double Mucosal Flap Anastomosis

Abstract: The aim of this study was to compare surgical outcomes of external dacryocystorhinostomy with or without double mucosal flap anastomosis. A retrospective chart review was performed for 205 sides of 178 patients diagnosed with nasolacrimal duct obstruction. Double-flap anastomosis was performed on 57 sides (double-flap group) and complete flap excision on 148 sides (no-flap group). Criteria for surgical success were defined as no or minimal intermittent epiphora and no reflux on lacrimal irrigation 12 months po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…We previously reported that the ex-DCR with two-flap anastomosis provided a 93.0% success rate (53 of 57 sides) and the ex-DCR without flap anastomosis success rate was 93.2% (138 of 148 sides) at postoperative 12 months 17. Another study of an endonasal DCR without flap preservation reported that 92.2% success (375 of 407 sides) was achieved at postoperative 3 months 18.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the ex-DCR with two-flap anastomosis provided a 93.0% success rate (53 of 57 sides) and the ex-DCR without flap anastomosis success rate was 93.2% (138 of 148 sides) at postoperative 12 months 17. Another study of an endonasal DCR without flap preservation reported that 92.2% success (375 of 407 sides) was achieved at postoperative 3 months 18.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of difference may be linked to the excision of the posterior flap. However, Takahashi et al reported comparable surgical outcomes between external DCR with double-flap anastomosis and flapless surgery [ 14 ], which indicates that even with preservation of the posterior flap, flapless external DCR could have a comparable success rate.…”
Section: Discussionmentioning
confidence: 99%
“…The one-flap technique was reportedly as effective as the two-flap technique [ 12 ]. Currently, there is a new modification described by several authors, in which external DCR is performed with neither anterior nor posterior flaps [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…External DCR without flap anastomosis has also been applied in a majority of cases in a study done by Takahashi et al 5 This technique demonstrated a success rate as good as external DCR with double-flap. The author compared the surgical outcomes of 205 external DCR surgeries divided into double-flap group and no-flap group.…”
Section: Discussionmentioning
confidence: 99%